Effect Of Lathe Machining Parameters On Machining Characteristics Towards Mild Steel (AISI 1020) Using RSM - Mansoor, Mohd Sufriansyah (2019)
This project investigates the effect of lathe machining parameters on machining characteristics towards mild steel (AISI 1020) using Response Surface Method. The machining parameters selected on the experimental project are cutting speed (75m/min – 125m/min), feed rate (0.2mm/rev – 0.4mm/rev) and depth of cut (0.1mm-1.5mm). RSM using Box-Behnken was used to determine the most influential paremeters affected on the experimental response, investigate corelation between process parameters towards response and also to determine the optimum cutting parameters value that give minimum surface roughness and maximum material removal rate and hardness. There were 17 numbers of experiment has been conducted using the CNC lathe machine. The result collected was to optimize using RSM meanwhile P-value and R-squared were calculated using analysis of variance (ANOVA). From the result analysis obtained feed rate was the most influential parameters towards the surface roughness which contributes 53.88% of effect. Further, depth of cut and cutting speed are the most significant factor affected the material removal rate and hardness which contributes 66.78% and 37.40% of effect respectively. Interaction between process parameters was obtain and analyse towards surface roughness, material removal rate amd hardness. It found that, surface roughness value is decrease when the machine parameters at high cutting speed with low feed rate and depth of cut. Furthur, material removal rate increase when the machine parameters are at high cutting speed, feed rate and depth of cut. Meanwhile, when the machine parameters of cutting speed, feed rate and depth of cut are at middle value, the hardness value is significantly at highest value. Lastly, multiple optimization is perform and it shows that The combination of 101.2626 m/min cutting speed, 0.2444 mm/rev feed rate and the depth of 1.5 mm has a desirability of 0.6982 and the predicted values of MRR, surface roughness and hardness are 240.3743 g/min, 2.0669 µm and 44.3187 HRA respectively. Thus, all the objective of this project is achived and the optimal parameters are suceffully obtained to increase efficiency of machining process.